Polyparasitism and zoonotic parasites in dogs from a rural area of the Argentine Chaco - Enriquez, Gustavo Fabián; Macchiaverna, Natalia Paula; Argibay, Hernán Darío; Lopez Arias, Ludmila Sol; Farber, Marisa Diana; Gürtler, Ricardo Esteban; Cardinal, Martha Victoria; Garbossa, Graciela (Elsevier, 2019)
Dogs play an important role as reservoirs and hosts of multiple pathogens shared with humans and wildlife, which contribute significantly to the global burden of disease. Here, we assessed the occurrence of a broad range of zoonotic and non-zoonotic parasites in dogs from a rural area in the humid Chaco; determined the occurrence of polyparasitism; and explored its association with selected risk factors. In total, 212 dogs were examined serologically to determine Trypanosoma cruzi infection and 152 of them also were examined for Ehrlichia canis, Borrelia bugderfori, Anaplasma phagocitophylum, Dirofilaria immitis and Toxoplasma gondii. Fecal samples from 85 dogs were examined for intestinal parasites. Seventeen parasite species were seen, 77% of which are zoonotic. The most prevalent parasites were Ancylostoma caninum (68.2%), T. gondii (55.3%, first report for dogs in Argentina), Giardia sp. (25.9%), Cryptosporidium sp. (20.0%), T. cruzi (16.5%), trematodes (15.3%) and Toxocara canis (14.1%). Polyparasitism was found in 96% of the dogs, with up to six parasite species in a single dog, and was significantly associated with age of dog but not with host body condition or sex. The most frequent pair of parasites found together were T. gondii-A. caninum (46%), A. caninum-T. cruzi (34%) and T. gondii-T. cruzi (27%). The prevalence of anemia and leukocytosis was significantly higher in dogs showing the worst body condition. Our findings likely reflect structural poverty, poor sanitation and lack of a safe water supply. Importantly, many of the prevalent parasites seen are threats to human health.